О временной природе конкурентоспособности, экономического потенциала и потенциала развития предприятия - Шпак, Сергей Александрович (НТУ "ХПИ", 2018)
Исследована временная природа конкурентоспособности, экономического потенциала и потенциала развития предприятия и их взаимосвязи. Установлено, что экономический потенциал и потенциал развития являются точечными по времени признаками и характеризует предельные возможности генерирования прибыли и структурной адаптации предприятия, а конкурентоспособность, отражая способность предприятия генерировать приемлемую прибыль на длительной основе, является интегральным по времени признаком, уровень которого обусловливается экономическим потенциалом и потенциалом развития.

Contents and time-dependent nature of the key notions of enterprise economics directly connected with development and strategic management of industrial enterprises and revealing close links between them are investigated. Within the competitiveness concept of enterprises, their economic potential and potential for development as capabilities for inherent activities of enterprises, it is identified that the economic potential and potential for development to be pointwise features of enterprises over time characterize the critical capabilities for profit generation of the acceptable level and for structural adaptation to be a tool for upscaling the economic potential respectively. It is demonstrated that competitiveness as a feature of enterprises reflects their critical capabilities for generation of acceptable profit on the long term basis, is an integral feature over the overall planning horizon of profit, which level is dictated by the economic potential and potential for development, and this preconditions relevancy of the search problem for rational compromise between enhancement of the economic potential and potential for development under conditions of the permanently varying competitive environment.
About the temporary nature of competitiveness, economic potential and potential of enterprise development
Keywords: промышленное предприятие; доход; прибыль; стратегическое управление; industrial enterprise; development potential